1954
DOI: 10.1042/bj0570255
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro enzymic hydroxylation of steroid hormones. 1. Factors influencing the enzymic 11β-hydroxylation of 11-deoxycorticosterone

Abstract: BY A. C. BROWNIE AND J. K. GRANT ' cyclophorase' system (Green, Loomis & Auerbach, 1948). 'Cyclophorase' preparations, however, are not cytoplasmically homogeneous (Harman, 1950). Credit for showing that 1 1l,-hydroxylating enzymes are associated with adrenal-cell particles which by their method of preparation were mainly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

1957
1957
1974
1974

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 25 publications
5
32
0
Order By: Relevance
“…The high adenyl cyclase activity of adrenal cortex mitochondria as found by Hechter et al [3] is apriori compatible with the reported stimulation, by cyclic AMP, of the 1 l/3-hydroxylation in adrenal cortex [8] and with the mitochondrial localization of 1 lo-hydroxylase [9]. However, since the purity of the mitochondrial preparations obtained by these authors was assessed only by electron microscopy and not on enzymatic criteria, we decided to undertake a more detailed investigation on the subcellular distribution of adenyl cyclase in adrenal cortex.…”
Section: Introductionsupporting
confidence: 84%
“…The high adenyl cyclase activity of adrenal cortex mitochondria as found by Hechter et al [3] is apriori compatible with the reported stimulation, by cyclic AMP, of the 1 l/3-hydroxylation in adrenal cortex [8] and with the mitochondrial localization of 1 lo-hydroxylase [9]. However, since the purity of the mitochondrial preparations obtained by these authors was assessed only by electron microscopy and not on enzymatic criteria, we decided to undertake a more detailed investigation on the subcellular distribution of adenyl cyclase in adrenal cortex.…”
Section: Introductionsupporting
confidence: 84%
“…The situation has been assumed by most workers to be identical with that pertaining in adrenal-cortex mitochondria where the ability of tricarboxylic acid cycle intermediates to support steroid hydroxylation has been observed by several groups of investigators [7-91. It has been demonstrated that respiration and oxidative phosphorylation are inhibited by deoxycorticosterone hydroxylation when they share a common electron donor and Cammer and Estrabrook, and Sauer [lo, 111 suggested that tricarboxylic-acidcycle intermediates supported 11B-hydroxylation by reducing NADP+ intramitochondrially via a trans-mycin or cyanide [8,[12][13][14], suggested that transfer of reducing power for steroid hydroxylation was dependent upon oxidative phosphorylation. Estabrook and coworkers [lo] proposed that in the adrenal cortex the two mitochondria1 electron-transfer chains were connected via an energy-dependent transhydrogenase.…”
mentioning
confidence: 99%
“…This would appear reasonable if the endoplasmic reticulum can be considered an intracytoplasmic extension of the extracellular space which acts as a conduit from cell to exterior (Carr, 1960) but in this respect the distinction between the endoplasmic reticulum and the Golgiform apparatus is apt to be confusing both morphologically and terminologically. In the light of the ultrastructural evidence it seems no mere coincidence that biochemical studies have shown the two enzymes involved in the last stages of corticosteroidogenesis to be associated with the mitochondria and the endoplasmic reticulum respectively (Brownie & Grant, 1954;Grant, 1962;Plager & Samuels, 1954). Thus corticosteroid might gain the cell exterior via the endoplasmic reticulum which here may exist as a tubular system opening to the extracellular or subendothelial space; the possibility that exocytosis or reverse pinocytosis participates to some extent in this scheme must obviously also be considered.…”
Section: E K Matthews and M Saffranmentioning
confidence: 99%